2016
DOI: 10.1590/0104-07072016002290015
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Child Risk Factors Associated With Neonatal Mortality

Abstract: This was a cross-sectional study that investigated maternal and child factors associated with neonatal mortality. Data was obtained from the Live Births and Mortality Information Systems integrated by linkage. A total of 9,349 live births and 78 deaths in the neonatal period, which occurred in 2010 in Cuiabá-MT were analyzed. Univariate and multivariate analyzes were performed. In the multiple logistic regression, neonatal mortality was associated with: maternal age less than 20 years; prematurity; low birth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
1
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 21 publications
7
20
1
12
Order By: Relevance
“…In this study, the variable low schooling presented itself as a protective factor in the quadrennium 2005-2008, but it is known that the lack of information is an aggravating factor in health, being the low schooling a predominant Brazilian feature in the profile of neonatal deaths. 5,6,21 It is emphasized that, from 2009 to 2016, the low schooling was demonstrated as a risk to the fissure, corroborating the literature. 22 In Argentina it was found that the maternal and paternal schooling are also considered risk factors for fissures, 18 as well as in Vietnam, where the low schooling is associated with higher chances of fissure.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, the variable low schooling presented itself as a protective factor in the quadrennium 2005-2008, but it is known that the lack of information is an aggravating factor in health, being the low schooling a predominant Brazilian feature in the profile of neonatal deaths. 5,6,21 It is emphasized that, from 2009 to 2016, the low schooling was demonstrated as a risk to the fissure, corroborating the literature. 22 In Argentina it was found that the maternal and paternal schooling are also considered risk factors for fissures, 18 as well as in Vietnam, where the low schooling is associated with higher chances of fissure.…”
Section: Discussionsupporting
confidence: 77%
“…16,20 However, paradoxically, we found a case-control study conducted with 340 babies in Vietnam, which pointed out as the age group most affected, the population aged up to 24 years old. 21 In Argentina, a casecontrol study with 13,444 babies also showed that women aged less than 19 had more chances of presenting children with cleft lip and/or cleft palate. 18 It is understood that the association between maternal age and development of cleft has controversies in the literature, although the results of this study have pointed out a higher risk of malfunction in mothers of advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…24 Regarding neonatal outcomes, regardless of the method used for induction (Foley catheter, Misoprostol and Oxytocin), there were favorable results; in the end, 91.2% of newborns presented Apgar greater than or equal to 7 in the first minute, demonstrating the quality of delivery care and, consequently, the favorable conditions of newborn vitality. 25 It should be noted that only 6.5% went to the neonatal ICU and that the majority of these cases were related to prematurity.…”
Section: -20mentioning
confidence: 98%
“…Child who have low birth weight children have immature immune function are also prone to have increased risk of disease, lower IQ and cognitive disabilities which could affect their performance in school, job opportunities as adults and may develop chronic illness like diabetes and coronary heart disease in adult hood (Gaiva, Fujimori, & Sato, 2016). Low Birth Weight of is also known to cause cerebral palsy more frequent hospitalization for all illness, more hearing and visual disability more behavioral disorders (Kliegman, Behrman, Jenson, & Stanton, 2007).…”
Section: Introductionmentioning
confidence: 99%